2013
DOI: 10.3324/haematol.2013.083840
|View full text |Cite
|
Sign up to set email alerts
|

Hematologic variables and venous thrombosis: red cell distribution width and blood monocyte count are associated with an increased risk

Abstract: Odds ratios and their 95% confidence intervals (95% CI) were cal- open-access paper. doi:10.3324/haematol.2013 Recent studies suggest that leukocytes and erythrocytes play a role in coagulation. However, whether leukocytes, erythrocytes and other hematologic variables are associated with risk of venous thrombosis is not well known. To study this, we used data from 2473 patients with venous thrombosis and 2935 controls. The variables assessed were: total leukocytes, granulocytes, lymphocytes, monocytes, hematoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
94
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(108 citation statements)
references
References 41 publications
11
94
1
2
Order By: Relevance
“…These results confirm and extend what has been reported previously in other studies [11,12]. However in our study we found a highly statistically significance association of monocytes and previous VTE (OR 2.47 and p value 2.49 ×10 -4 ).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…These results confirm and extend what has been reported previously in other studies [11,12]. However in our study we found a highly statistically significance association of monocytes and previous VTE (OR 2.47 and p value 2.49 ×10 -4 ).…”
Section: Discussionsupporting
confidence: 93%
“…It is obvious that our results do not exclude the possibility that there is a relationship between other types of leukocytes and thrombosis. We don't know if there is a causal relationship between high monocyte levels and the disease because our sample has been taken after the thrombotic episode, but, our findings, are in line of Tromsø and MEGA studies [11,12] and they support that high monocyte counts are in association with past VTE. We believe that our results provide a firm foundation for additional studies and they suggest that a high monocyte count are related with VTE risk and could be a useful parameter in future prediction models.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The ROC analysis showed that the best cut-off value is 13.6 % for RDW and it has a predictive value for differentiation. In studies performed by Rezende et al [24], Cay et al [25], and Ozsu et al [26], they found that high RDW level was associated with VTE and it was also an independent risk factor for mortality and VTE diagnosis. Zorlu et al [27] found that RDW seems to aid in the risk stratification of patients with acute PE with RDW [14.6.…”
Section: Discussionmentioning
confidence: 96%